Pacto Nacional pela Alfabetização na Idade Certa: formação de professores alfabetizadores no âmbito da UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This thesis is part of the History and Educational Policies research line of the Graduate Program in Education and has as its object of study the National Pact for Literacy in the Right Age, implemented from 2013 throughout the country. We start, therefore, from the thesis that the partnership between the Ministry of Education - MEC and universities contributed to the strengthening of teacher education, as the university is the privileged space to produce knowledge, favoring the deepening and updating of knowledge that are necessary for an emancipatory, critical and creative pedagogical practice. The following question was outlined as the central research problem: what were the limits and possibilities for the formation of literacy teachers in the context of the National Pact for Literacy in the Right Age, within the State University of Ponta Grossa? To answer the problem, the following objectives were defined: to contextualize the educational policies for training literacy teachers in Brazil from the 1990s onwards, and the influence of international organizations for the formulation and implementation of these policies; understand the training of literacy teachers in the National Pact for Literacy in the Right Age, its structure, objectives and goals set out in official documents; characterize the actions proposed by the PNAIC, establishing a relationship between them and the training actions developed within the State University of Ponta Grossa - UEPG. The study presupposes the historical-dialectical materialism, used as a guideline for the analyzes carried out and the theoretical contribution of the following authors: Duarte (2004), Shiroma; Campos and Garcia (2005), Saviani (2007, 2009, 2013, 2016) Shiroma and Evangelista (2015), Klein; Galindo and D'Água (2016) and MAZEU (2007). To undertake the study, the investigation was carried out through bibliographical and documentary research with analysis of primary and secondary sources. The results allow us to infer that teacher education policies are characterized as government policies, being marked by the discontinuity of actions. However, public universities play an important role in articulating the initial and continuing training of Basic Education teachers. Through their studies and research, they seek to develop a solid education, based on the assumptions of an emancipatory education and in accordance with the reality of the course participants.
Keywords: Políticas Educacionais; Pacto Nacional pela Alfabetização na Idade Certa; Formação de Alfabetizadores; Educational Policies; National Pact for Literacy at the Right Age; Literacy Training; CNPQ::CIENCIAS HUMANAS::EDUCACAO